Ingestão de cálcio e de fósforo em crianças de três a doze anos deidade, de duas escolas, pública e particular, de Belo Horizonte, MG - Paula Lustosa Martins (2008)
The feeding of the child has been always detached, but with bigger emphasis in the present time. The function of the alimentary standards, in the last few decades, has suffered great changes. It is known that the nutrition during infancy and the adolescence intervenes with the health of the adult, mainly for its paper in preventing chronic illnesses such as osteoporosis and arterial hypertension. Under the influence of the modern life, of the media and the socioeconomics conditions, it is shown that the diet is deficient in some nutrients, nowadays, that can not only compromise the health of these children and adolescents, but also, influence in negative way their future health. Among these nutrients the minerals that are especially distinguished are calcium and phosphorus that are basic for the reach of the full bone health. In this study the diets of 312 students were evaluated, between three and 12 years of age, of two schools - a public and another particular one - of Belo Horizonte, with theobjective of evaluate quantitatively the alimentary ingestion of calcium and phosphorus, through alimentary registers of three days, self-applicable. The results obtained were compared with the current recommendations of ingestion for the participants of the two schools and with two parameters of socioeconomics evaluation for familiar income and themothers schooling. In accordance with the references adopted internationally, calcium ingestion was inadequate, in a great percentage of children, mainly in the age between 9 and 12 years, especially in women of the particular schools. There were no significant differences between the students of the two schools related to the familiar income and the mothers schooling. However, a great number of students of the particular school ingested minor amount of calcium when compared with those of the public school. Phosphorus ingestion was equal or bigger than the current recommendations.